Enforcement Of Criminal Law Against Abuse Of Immigration Permit According To Republic Of Indonesia Law No. 6 Of 2011 Concerning Immigration - La Ode Bunga Ali (Jurnal Hukum Volkgeist, 2023)
The scope of the visa-free facility is too broad which includes tourism, socio-cultural, and business activities, which was originally intended to strictly regulate visa-free facilities, but after the provision of visa-free facilities in the BVKS which has a wider scope, violations of the visa-free facility are still found. that. So that the aims and objectives of Free Social Visit Visa (BVKS) as a substitute for Free Tourist Visa (BVW), were not achieved, instead they were used by foreigners as a way for illegal immigrants to enter Indonesia. However, the General Explanation of Law No. 6 of 2011 concerning immigration emphasizes that for foreigners, services and supervision in the field of immigration are carried out with a "selective" principle (selective policy). Based on this principle, only foreigners who are allowed to enter Indonesia are foreigners who provide benefits for the welfare of the people, nation, and state of the Republic of Indonesia and do not endanger security and order, nor are they hostile towards the people or towards the Indonesian state based on Pancasila and the Law. -The 1945 Constitution. In terms of handling this, it is closely related to matters of supervision, both tourists entering or leaving the territory of the Republic of Indonesia, and carrying out activities in the territory of the Republic of Indonesia. Preventive countermeasures are countermeasures carried out in an effort to prevent or maintain the possibility of an immigration crime, in this case, namely the crime of misusing immigration permits. Meanwhile, in repressive measures, this can be done by way of punishment, deportation, or blacklisting. It is better if the provision of visa-free facilities is reviewed and returned to the background of the provision of these facilities, namely only for tourism.